Control Strategies Application in Wind Power System Technology: A Literature Review - Mensou Sara; Essadki Ahmed; Nasser Tamou (EPJ Web of Conferences)
Renewable energy has experienced rapid growth worldwide, as it offers the most effective solution for generating electricity in a clean and sustainable manner. It helps protect the environment and reduces pollution caused by the extensive use of traditional fossil fuels and nuclear energy. There are several topologies of renewable energy systems: Photovoltaic systems, wind systems, biomass, hydroelectric, and marine energy. Among renewable options, wind power is recognized as both exceptionally clean and highly efficient. It provides a safe and environmentally friendly way to generate electricity, which has led to its growing integration into electrical grids. This paper begins with an overview of the historical development of wind turbine installations worldwide. Then, a mathematical model of wind turbine technology was given. Finally the paper provides a literature review of wind turbine control strategies and a comparative study between some control technologies that was published recently.